(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This study investigates the influence of social media on e-commerce in Calabar, analyzing how platforms like Facebook, Instagram, WhatsApp, and Twitter (now X) have revolutionized company practices and customer interaction in the digital economy. As internet and mobile technology proliferate in Calabar, Cross River State, social media has emerged as an essential instrument for entrepreneurs, small and medium companies (SMEs), and large corporations to promote products, expand their reach, and streamline transactions. The research examines the degree to which social media impacts consumer behaviour, brand visibility, and business expansion in the local setting. It evaluates the techniques utilized by enterprises to capitalize on these platforms and the obstacles they encounter, including trust, digital literacy, and logistical concerns. The study employs an interdisciplinary methodology that includes surveys, interviews, and online content analysis to furnish empirical data regarding user interaction, engagement levels, and conversion rates associated with social media marketing. Research indicates that social media has markedly improved the visibility and operational efficacy of numerous e-commerce enterprises in Calabar; however, obstacles persist in infrastructure and trust development.